Innovation of Dynamic Cost Management and Goal Achievement: An Empirical Investigation of Electronics and Electrical Manufacturing Businesses in Thailand - Wangcharoendate, Suwan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The objective of this study is to empirically investigate the effects of innovation of dynamic cost management on goal achievement through cost utilization fitness, productivity efficiency proficiency and value enhancement. Furthermore, the moderating effect of organizational learning capability is also investigated. The electronics and electrical manufacturing businesses in Thailand, 303 companies, are used as the samples. Questionnaire was used to collect data. Data were then analyzed by using the Ordinary Least Squares (OLS) method of regression analysis. Results indicate that innovation of dynamic cost management has positive impact on goal achievement through consequences as the mediators. In addition, for moderating effects, organizational learning capability has shown partially positive supported between dynamic cost management innovation and consequences. The results can be a useful cost management process link to operation, and to enhance its success via dynamic competitive advantage and continuous corporate survival.